1998
DOI: 10.1046/j.1365-2664.1998.3540504.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced applications of metaldehyde pellets for reliable control of the slug pests Arion lusitanicus and Deroceras reticulatum in oilseed rape adjacent to sown wildflower strips

Abstract: Summary Slugs have been shown to cause severe damage in oilseed rape crops adjacent to sown wildflower strips. Rape can be protected from this damage by broadcasting a recommended dose of metaldehyde over the whole field area. This paper investigates whether severe slug damage can be prevented by applications of metaldehyde just along the wildflower strips thereby reducing the input of chemical molluscicide. In this study, untreated control plots suffered severe crop loss at 1 m from all wildflower strips st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
3
19
0
3
Order By: Relevance
“…Damage was more severe in moist soil possibly due to the moisture causing bait dissolution, rendering them ineffective. This agrees with the work of Friedli and Frank (1998), who reported that in field-plots, with a high slug density in humid months, a further application of molluscicide, to prevent severe slug damage, was necessary. In addition, in Experiment B, where it rained after treatment application, generally there were a lower number of plants than in Experiment A.…”
Section: Discussionsupporting
confidence: 92%
“…Damage was more severe in moist soil possibly due to the moisture causing bait dissolution, rendering them ineffective. This agrees with the work of Friedli and Frank (1998), who reported that in field-plots, with a high slug density in humid months, a further application of molluscicide, to prevent severe slug damage, was necessary. In addition, in Experiment B, where it rained after treatment application, generally there were a lower number of plants than in Experiment A.…”
Section: Discussionsupporting
confidence: 92%
“…Although it was not possible to quantify slug density in this study, there is no compelling reason to believe that slug densities were atypically high. The experiment was surrounded by a 20‐meter wide band of close mown grass; tall vegetation associated with high slug density (Pallant 1974; Friedli & Frank 1998) was restricted to the unmown experimental block.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, A. lusitanicus seems to have spread throughout Europe (von Proschwitz 1993). Nowadays, it is one of the most important slug pests on farmland and private gardens in many European countries (Frank 1998;Friedli & Frank 1998;Speiser 1999;Sulzberger 1996;von Proschwitz 1993). A. lusitanicus is responsible of up to 90% of the damages caused by slugs in the gardens in Southern Germany (Sulzberger 1996).…”
Section: Introductionmentioning
confidence: 99%